Role of nerves in enteric infection - Spiller, R C (Copyright 2002 by Gut, 2002)
Peripheral and central effects of enteric infection are considered. Nerves play a vital part in the immediate response to enteric infection, promoting pathogen expulsion by orchestrating intestinal secretion and propulsive motor patterns. Laboratory studies indicate that therapeutic agents aimed at modulating the neural response can profoundly alter the outcome of infection. As our understanding of the role of nerves increases, exciting new targets for therapeutic intervention will emerge in both acute and chronic disorders induced by enteric infection.